Exploring the Reemergence of Social Class in Contemporary Society: An Analysis of the Influence of Social Class on Individuals’ Economic Perceptions - Stancea, Andreea; Ciocîrlan, Cecilia; Benga, Corina (Calitatea Vieții, 2024)
This article aims at investigating the contemporary impact of social class on economic perceptions in Romania. Contrary to arguments suggesting the diminishing relevance of social class in the face of new social divisions and a shift away from class-based politics, this research posits that social class remains a critical determinant of individuals' views on economic conditions. To test the hypotheses, this article employs individual-level data from the 2012 Romanian Election Study (RES), with a sample of 1.300 participants, all of whom are aged 18 and above. Using OLS regression models, the analysis seeks to deepen understanding of how social stratification shapes economic outlooks and, consequently, political choices in a changing world. The findings underscore the importance of social class in shaping individuals' economic interpretation, contributing to a deeper academic discourse on the connections between social stratification, economic viewpoints, and democratic involvement.